2021
DOI: 10.1302/1863-2548.15.210015
|View full text |Cite
|
Sign up to set email alerts
|

Tübingen hip flexion splint for the treatment of developmental dysplasia of the hip in children younger than six months age: A meta-analysis

Abstract: Purpose To investigate the success rate of the Tübingen hip flexion splint (THFS) for the treatment of developmental dysplasia of the hip (DDH), of different severity as per the Graf classification, among infants younger than six months of age. The type and incidence rate of complications associated with THFS treatment were also evaluated. Methods The following databases were searched using keywords and limited for age less than six months: PubMed, Embase, Web of Science, Cochrane Library, and SinoMed, between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
1
1
1
Order By: Relevance
“…This is in accordance to our data with 98.9% success rate of type D and 95.3% success rate of type III hips. On the other hand, the success rate of 32.0% for type IV hips was very low (with statistically low heterogeneity in the study group) [17]. These data were significantly inferior to the results of the present study showing a success rate of 81.2% for type IV hips.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is in accordance to our data with 98.9% success rate of type D and 95.3% success rate of type III hips. On the other hand, the success rate of 32.0% for type IV hips was very low (with statistically low heterogeneity in the study group) [17]. These data were significantly inferior to the results of the present study showing a success rate of 81.2% for type IV hips.…”
Section: Discussioncontrasting
confidence: 99%
“…The above-mentioned success rate of 95.5% is comparable with previous studies, which examined the therapy of ultrasound unstable hips with the Tübingen splint. Here, success rates of 92.3-98.0% were observed [10][11][12]17]. Seidl et al found in their study with 52 ultrasound unstable hips a success rate of 98.0% [11].…”
Section: Discussionmentioning
confidence: 92%
“…Laikysenos defektai, skoliozė ir skausmingi funkciniai bei struktūriniai juosmeninės ir kryžmeninės stuburo dalių pakitimai priskiriami prie negydomų arba nepakankamai gydomų KVD patologijos sukeltų raumenų ir skeleto funkcijų sutrikimų [20]. Dėl šių bei kitų panašių anomalijų, atsiradusių ankstyvųjų ar vėlyvųjų problemų, susijusių su KVD, sutrinka statinės bei dinaminės funkcijos [51]. KVD patologijos kontekste svarbus vidurinis sėdmens raumuo, priklausantis šlaunies atitraukiamųjų raumenų grupei [48].…”
unclassified